2015
DOI: 10.1002/erv.2379
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Disorder‐Related Autobiographical Memory in Acute Anorexia Nervosa Patients

Abstract: This study detects disorder-related autobiographical memory alterations in AN, which are intensified in response to symptom-related cues. The findings are discussed with regard to their maladaptive function in emotion regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 60 publications
4
31
0
Order By: Relevance
“…The literature on memory bias in patients with AN suggests no biases for memories triggered by depression-related words including “rejection” and “criticism” ( 57 ) and no differences in terms of frequency of negatively valenced memories ( 57 , 58 ) when patients are compared to healthy controls. However, there is some indication that patients with AN tend to recall fewer and more general (vs. specific) memories when these are cued by food- or body-related words ( 57 ). Taken together, these findings do not seem to suggest that negative interpersonal memories are easily biased in patients with eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on memory bias in patients with AN suggests no biases for memories triggered by depression-related words including “rejection” and “criticism” ( 57 ) and no differences in terms of frequency of negatively valenced memories ( 57 , 58 ) when patients are compared to healthy controls. However, there is some indication that patients with AN tend to recall fewer and more general (vs. specific) memories when these are cued by food- or body-related words ( 57 ). Taken together, these findings do not seem to suggest that negative interpersonal memories are easily biased in patients with eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A power analysis was conducted using G*Power (version 3.1.9.2) (Faul, Erdfelder, Buchner, & Lang, 2009). On the basis of previous studies using word stimuli for memory performance in AN (Bomba et al, 2014;Huber et al, 2015), a medium to large effect size can be assumed for group differences between AN patients and CO healthy controls. For AN patients, differences in memory performance for the recall of various types of word stimuli have been shown, with large effect sizes.…”
Section: Sample Size Estimation and Power Analysismentioning
confidence: 99%
“…These alterations are likely to be involved in several changes observed: besides a reduction in food intake and body weight also an intestinal barrier dysfunction (Jésus et al, 2014), a disruption of neural development in the hippocampus (Chowdhury et al, 2014) and an impairment of memory function (Paulukat et al, 2016), increased anxiety (Kinzig and Hargrave, 2010) and the development of stress ulcers (Doerries et al, 1991), features also observed (Kline, 1979; Ghadirian et al, 1993; Swinbourne and Touyz, 2007; Huber et al, 2015; Kjaersdam Telleus et al, 2015) or suspected in patients with AN. Taken together, activity-based anorexia—despite the major limitation of being an animal model merely mimicking features of a disease—is likely a suited tool to study aspects of the pathogenesis of human AN.…”
Section: Introductionmentioning
confidence: 98%